Silver-Modified Nano-titania as an Antibacterial Agent and Photocatalyst - Tobaldi, D. M.
With the increasing demand for nanomaterials, it is essential that they are produced, where possible, by sustainable or \"green\" synthesis methods, avoiding environmentally harmful processes and solvents, with the aim of reducing the production of hazardous byproducts and wastes and minimizing environmental impact. In this work, Ag-modified titania nanoparticles (NPs) were synthesized via a green aqueous sol gel method. The products of the synthesis were thermally treated at 450 and 600 degrees C, and their photocatalytic (in liquid solid and gas solid phases) and antibacterial properties were assessed using both UV- and visible-light exposure. The microstructure and phase composition of the prepared samples were also characterized using advanced X-ray powder diffraction methods (whole powder pattern modeling). Results showed that both the amount of Ag and the thermal treatment greatly influenced not only the phase composition and microstructure but also the functional properties of the TiO2. The increasing levels of Ag retarded the anatase-to-rutile phase transition to a greater extent, and 2 mol % was the optimum amount of Ag for methylene blue photodegradation with both UV- and visible-light irradiation. When using a UV-light source, samples showed a much greater antibacterial activity toward Escherichia coli (E. coli; Gram-negative) than methicillin-resistant Staphylococcus aureous (Gram-positive). It was observed that UV light caused a change in the oxidation state of silver, from ionic silver to metallic (Ag+ -> Ag-0 NPs), this being detrimental for the antibacterial activity. However, under artificial white light irradiation this did not occur and the material kept its excellent antibacterial properties (higher activity than commercial P25); because of this, it could be suitable for use in health care, helping to greatly reduce the spread of Gram-negative type bacteria such as E. coli.